2001
DOI: 10.1093/molehr/7.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of nitric oxide in functional and regressing rat corpus luteum

Abstract: The present study investigated the effect of nitric oxide (NO) on the lifespan of the corpus luteum (CL). Using a competitive nitric oxide synthase (NOS) inhibitor, L-nitro arginine methyl ester (L-NAME, 600 micromol/l), and a long-life NO donor, diethyl-aminetriamine (DETA-NONOate, 10(-8), 10(-6) or 10(-4) mol/l), we found that in ovaries from rats at the mid stage of CL development, endogenous NO increased both glutathione (GSH) and progesterone production. However, during prostaglandin F(2 alpha) (PGF(2 alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 26 publications
7
62
1
1
Order By: Relevance
“…The reasons of rise may be increasing follicular diameters at 17β-estradiol levels, starting corpus luteum development at progesterone levels. The finding of increase NO levels supports the findings of other studies (22,26) which report that as the cycle progresses, sensitivity to NO increases and more NO is synthesized in the luteinized ovarium. In the luteal period, increase in the flow of blood ensures the formation of corpus luteum and maintains its functional characteristics (21).…”
Section: Discussionsupporting
confidence: 90%
“…The reasons of rise may be increasing follicular diameters at 17β-estradiol levels, starting corpus luteum development at progesterone levels. The finding of increase NO levels supports the findings of other studies (22,26) which report that as the cycle progresses, sensitivity to NO increases and more NO is synthesized in the luteinized ovarium. In the luteal period, increase in the flow of blood ensures the formation of corpus luteum and maintains its functional characteristics (21).…”
Section: Discussionsupporting
confidence: 90%
“…Further, we did not look at other NOS isoforms including neuronal or inducible NOS. However, we do hypothesize that one or both synthases may play a role in progesterone decrease, as NO has been proposed to regulate luteal steroidogenesis PGF 2a -induced luteal regression in sheep (Van Voorhis et al 1994, Jaroszewski & Hansel 2000, Motta et al 2001.…”
Section: Pgf 2a -Induced Luteal Regression In Sheepmentioning
confidence: 91%
“…Determining the profile of angiogenic factors responsible for vascular changes may prove to be important in determining how the composition of the CL is altered during regression. While there are several factors which have been shown to influence vascularity of different tissues, some of the primary regulators of ovarian angiogenesis and vascular function include: the vascular endothelial growth factor (VEGF) system (including the VEGF receptors and the neuropilins; Ferrara et al 1992, Shalaby et al 1995, Neufeld et al 1999, Stacker & Achen 1999, fibroblastic growth factors (FGF) and receptors (Klagsbrun & D'Amore 1991, Neuvians et al 2004a, the angiopoietins (ANGPT) and their receptor Tie-2 (Sato et al 1993, Davis & Yancopoulos 1999, Hazzard et al 2000, Wulff et al 2000, Tanaka et al 2004, the nitric oxide (NO) system (Motta et al 2001, Klipper et al 2004, Shi et al 2004, Al-Gubory et al 2005, and the renin-angiotensin system (Hansel & Blair 1996, Hayashi & Miyamoto 1999, Kobayashi et al 2001. While it is most certain that there are several other angiogenic factors playing a role in the regulation of vascular function, selected members from these families were investigated in the current experiment.…”
Section: Introductionmentioning
confidence: 99%
“…GSH is an antioxidant metabolite involved in reactions of oxide reduction, thus neutralizing oxidant species. It has been reported that antioxidant defenses are regulated by hormones (Motta & Gimeno 1997, Motta et al 2001a, 2001b, Tam et al 2003, Estevez et al 2004, Duarte et al 2005.…”
Section: Introductionmentioning
confidence: 99%